(untitled) (Journal of Decolonising Disciplines, 2021)
A PhD student shares part of her arts-based praxis process of developing a relational model of curriculum oriented towards reconciliation in Canada and South Africa by reflecting on a pilot course she offered at a university in Canada in 2018. This site-specific, media arts-based environmental education is intended for universities committed to walking the talk of decolonising education. Centered around water as a mirror of the state of our social relations and democracy, which it seeks to transform, the curriculum also facilitates public education and dialogue around the importance of healthy waterways amidst the pressures of climate change. Using a set of questions as a data analysis tool combined with narrative analysis of students’ videos, the researcher outlines the three most prominent relational sensibilities and abilities towards reconciliation cultivated by students through the program: (1) Knowledge Ecologies; (2) A Hopeful Social Imaginary; and (3) Embodied Ways of Knowing.